Exploring the SiCCT Gene Family and Its Role in Heading Date in Foxtail Millet - Li, Congcong; Ma, Jian; Wang, Genping; Li, Haiquan; Wang, Hailong; Wang, Guoliang; Jiang, Yanmiao; Liu, Yanan; Liu, Guiming; Liu, Guoqing; Cheng, Ruhong; Wang, Huan; et al. (Frontiers in Plant Science, 2022)
CCT transcription factors are involved in the regulation of photoperiod and abiotic stress in Arabidopsis and rice. It is not clear that how CCT gene family expand and regulate heading date in foxtail millet. In this study, we conducted a systematic analysis of the CCT gene family in foxtail millet. Thirty-nine CCT genes were identified and divided into four subfamilies based on functional motifs. Analysis showed that dispersed duplication played a predominant role in the expansion of CCT genes during evolution. Nucleotide diversity analysis suggested that genes in CONSTANS-like (COL) -like, CCT MOTIF FAMILY (CMF) - like, and pseudoreponse response regulator (PRR) -like subfamilies were subjected to selection. Fifteen CCT genes were colocalized with previous heading date quantitative trait loci (QTL) and genome-wide association analysis (GWAS) signals. Transgenic plants were then employed to confirm that overexpression of the CCT gene SiPRR37 delayed the heading date and increased plant height. Our study first investigated the characterization and expansion of the CCT family in foxtail millet and demonstrated the role of SiPRR37. These results lay a significant foundation for further research on the function of CCT genes and provide a cue for the regulation of heading date.